Groups of small cairns in northern Britain - a view from SW Scotland - Yates, M J (Proceedings of the Society of Antiquaries of Scotland, 1985)
An agricultural rather than a funerary explanation is sought for the small groups of cairns in Dumfries-Galloway, which appear to span the Sub-Boreal and Sub-Atlantic (3200 into 1st millennium BC).